HAWC as a Ground-Based Space-Weather Observatory - Alvarez, C.; Angeles Camacho, J. R.; Arteaga-Velázquez, J. C.; Arunbabu, K. P.; Avila Rojas, D.; Baghmanyan, V.; Belmont-Moreno, E.; BenZvi, S. Y.; Brisbois, C.; Caballero-Mora, K. S.; Capistrán, T.; Colín-Farias, P.; et al. (Solar Physics, 2021)
The High Altitude Water Cherenkov (HAWC) gamma-ray observatory is located close to the equator (latitude 18 ∘ N), at an altitude of 4100 m above sea level. HAWC has 295 water Cherenkov detectors (WCD), each containing four photomultiplier tubes (PMT). The main purpose of HAWC is the determination of the energy and arrival direction of very high energy gamma rays produced by energetic processes in the universe, HAWC also has a scaler system which counts the arrival of secondary particles to the detector. In this work we show that the scaler system of HAWC is an ideal instrument for solar modulation and space-weather studies due to its large area and high sensitivity. In order to prepare the scaler system for low energy heliospheric studies, we model and correct the efficiency variation of each PMT of the array, which result in a capability to measure variations > 0.01 % with high accuracy. Using the singular value decomposition method, we correct the rate deviations of all PMTs of the array, due to changes in efficiency, gain and operational voltage. We isolate and remove the atmospheric modulations of the PMTs count rates measured by the TDC-scaler data acquisition system. In particular, the atmospheric pressure at the HAWC site exhibits an oscillating behavior with a period of ∼12 hours and we make use of this periodic property to estimate the pressure coefficients for the HAWC TDC-scaler system. These corrections performed on the TDC-scaler system make the HAWC TDC-scaler system an ideal instrument for solar modulation and space-weather studies. As examples of this capability, we present the preliminary analysis of the solar modulation of cosmic rays at three time scales observed by HAWC, with an unprecedented accuracy.
CRIS-Team Scopus Importer:2021-06-18
Keywords: Atmospheric pressure modulation; Cosmic rays; Fast Fourier transform; Solar modulation